Endothelial Dysfunction and Altered Coagulation As Mediators of Thromboembolism in Behçet Disease - Butta, Nora V.; Fernández-Bello, Ihosvany; López-Longo, Francisco J.; Jiménez-Yuste, Víctor (Seminars in Thrombosis and Hemostasis, 2015)
Behçet disease (BD) is a rare multisystem, inflammatory disease of unknown etiology with vascular involvement and associated thrombogenicity. This review aims to describe the involvement of various mediators in endothelial cell damage and in the hypercoagulable state of BD. The scenario of the chronic inflammation present in BD shows an increased oxidative condition that contributes to endothelial cell damage and induces platelet, leukocyte, and endothelial cell activation through the release of proinflammatory cytokines and chemokines. These factors, together with the increased levels of homocysteine observed in BD patients, induce the endothelial cell expression of adhesion molecules (VCAM-1 and ICAM-1) and tissue factor; the release of cytokines, soluble CD40L (sCD40L), matrix metalloproteinase-9, and blood coagulation factor V; the inhibition of fibrinolysis; the disruption of nitric oxide metabolism; and the increase in platelet reactivity and lipid peroxidation. Endothelial cell dysfunction leads to a prothrombotic and antifibrinolytic phenotype in BD patients. Increased levels of homocysteine, fibrinogen, and plasminogen activator inhibitor type 1 seem to be involved in the procoagulant condition of this pathology that has been verified by end-point tests as well as by global coagulation tests.
Keywords: Behçet disease; endothelial cell dysfunction; procoagulant condition